2005
DOI: 10.1007/s00428-005-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Claudins 1, 3, 4 and 5 in gastric carcinoma, loss of claudin expression associates with the diffuse subtype

Abstract: In this study expression of claudins 1, 3, 4 and 5 were studied in 118 cases of gastric carcinoma and compared with proliferation, apoptosis and E-cadherin expression. Expression of all these claudins could be seen in gastric carcinoma, most prominently for claudin 4, and least expression was found for claudin 5. All claudins showed significantly more expression in gastric carcinomas of intestinal type. Their expression was significantly associated with each other. Expression of claudins 4 and 5 was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
98
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 20 publications
(25 reference statements)
6
98
2
2
Order By: Relevance
“…Although some investigators observed that claudin-1,-3,-4,-5 and -7 are reduced in diffuse type gastric cancer [38][39][40] , up-regulation of claudin-7 in intestinal type has also been reported 39,40 . Reports on the expression of claudin family in other types of cancer are also controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Although some investigators observed that claudin-1,-3,-4,-5 and -7 are reduced in diffuse type gastric cancer [38][39][40] , up-regulation of claudin-7 in intestinal type has also been reported 39,40 . Reports on the expression of claudin family in other types of cancer are also controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Hereby, a decreased presence of TJ proteins has been described for claudins 4, 18, and 23, ZO-1 as well as occludin, in part correlating with poor cancer differentiation (Kimura et al, 1997;Katoh, 2005;Lee et al, 2005;Sanada et al, 2006). An increased presence of TJ proteins when compared with normal gastric mucosa has been described for claudins 1, 3, 4, 5, and 7, particularly in intestinal-type adenocarcinomas (Johnson et al, 2005;Resnick et al, 2005;Hewitt et al, 2006;Soini et al, 2006;Wu et al, 2006). These observations point to a complex deregulation of TJ proteins in gastric carcinogenesis, being suggestive of a cancer inhibitory role of downregulated TJ proteins.…”
mentioning
confidence: 93%
“…[11][12][13][14][15] In stomach cancer, claudin-4 was identified as one of the markers of gastric adenocarcinoma precursor lesions 16 and found to be most prominently overexpressed among claudins in gastric adenocarcinoma. 17 Moreover, its expression was reported to be lower in poorly differentiated diffuse-type gastric cancer than in well-differentiated intestinal-type gastric cancer, suggesting its possible role in determining the diffuse phenotype. [17][18][19] In addition to its aberrant expression in several cancers, claudin-4 expression has been shown to be associated with prognosis in breast or bladder cancer, 20,21 and has a role in invasiveness and metastatic potential of pancreatic cancer cell, 22 as well as it induces angiogenic factors in ovarian cancer.…”
mentioning
confidence: 99%
“…17 Moreover, its expression was reported to be lower in poorly differentiated diffuse-type gastric cancer than in well-differentiated intestinal-type gastric cancer, suggesting its possible role in determining the diffuse phenotype. [17][18][19] In addition to its aberrant expression in several cancers, claudin-4 expression has been shown to be associated with prognosis in breast or bladder cancer, 20,21 and has a role in invasiveness and metastatic potential of pancreatic cancer cell, 22 as well as it induces angiogenic factors in ovarian cancer. 23 However, although there have been a few studies into the association of claudin-4 expression and prognosis, it remains unclear whether claudin-4 expression is associated with clinical outcomes in gastric cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation